2010 10th IEEE-RAS International Conference on Humanoid Robots 2010
DOI: 10.1109/ichr.2010.5686291
|View full text |Cite
|
Sign up to set email alerts
|

Omni-directional closed-loop walk for NAO

Abstract: Abstract-This paper describes the new walk algorithm implemented on the NAO robot. NAO is a small fully actuated biped robot provided by the French company Aldebaran Robotics. Since the beginning of the company in July 2005, a major goal has been the development of robust walk for the robot. After 5 years of mecatronic design and improvements in robustness of the robot (7 prototypes) and multiple prototypes of humanoid dynamic walk algorithm, an omni-directional walk robust against small obstacles is now avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 13 publications
0
64
0
2
Order By: Relevance
“…7, it can be observed that the left knee angles of the robot did not appear to match to those of the reference skeleton, e.g., during toe off. There are two causes to this difference: 1) the constraint on KneePitch angle, in (15), and 2) the constraint on swing foot positions, in (12). The former limits the change of KneePitch angle within a predefined range while the latter limits a swing foot height to be between the ground level and maximum swing foot height.…”
Section: B Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7, it can be observed that the left knee angles of the robot did not appear to match to those of the reference skeleton, e.g., during toe off. There are two causes to this difference: 1) the constraint on KneePitch angle, in (15), and 2) the constraint on swing foot positions, in (12). The former limits the change of KneePitch angle within a predefined range while the latter limits a swing foot height to be between the ground level and maximum swing foot height.…”
Section: B Experimental Resultsmentioning
confidence: 99%
“…example, Gouaillier et al [12] generated an omni-directional walking motion for NAO robot based on a preview controller. Massah et al [13] introduced a method for planning the robot's walking on slopes.…”
Section: Introductionmentioning
confidence: 99%
“…This calculation could be especially useful for walking algorithms that embed closed loop control of torso inclination like the technique adopted by Gouaillier et al [16] or the one used by Glaser et al [17] for the NAO robot. However, if we take the same foot trajectory shape for the inclined torso as for the straight torso to design longitudinal and lateral walking patterns where feet remain parallel, the coupled yaw-pitch joint must also be controlled, this is because the roll axis at the hip is no more horizontal and therefore cannot move the foot in the frontal plane without actuating the coupled joint.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been successfully implemented in the NAO humanoid robot as its core WPG (Gouaillier et al, 2010).…”
Section: 1mentioning
confidence: 99%